The FBMD-1 stroma cell line secretes a unique moiety which can increase retroviral transduction of lineage-committed and primitive human peripheral blood progenitor cells - Buß, Eike Christian; Schiedlmeier, Bernhard; Ho, Anthony Dick; Zeller, W. Jens; Frühauf, Stefan (Cancer gene therapy, 2001)
Peripheral blood progenitor cells are a prime target for gene therapy approaches. As recent data point to the relevance of soluble stroma factors for the efficient transduction of progenitor cells, we tested the stroma-conditioned medium (SCM) of the two cell lines FBMD-1 and L88/5 as well as desulfated and O-sulfated heparin (HS dS and HS OS) for their effect on transduction of peripheral blood progenitor cells. We transduced CD34 + cells of nine tumor patients with the retroviral SF-MDR vector containing the human multidrug resistance 1 ( MDR 1) gene under serum-free conditions on the fibronectin fragment CH-296 with or without SCM.